Accuracy of ultrasound measurement of progressive change in occlusal enamel thickness - TAĞTEKİN, DİLEK; YANIKOĞLU, FUNDA (MOSBY-ELSEVIER, 2005)
Objective. To evaluate the effectiveness of ultrasound on measuring the thickness of enamel in abrasion. Study design. Flat areas on occlusal surfaces of 20 premolar teeth were marked. Two initial ultrasonic measurements on marked areas were obtained by the first researcher. Then the tooth was measured in the axial direction with a compass. The cusp tips were abraded by an abrasive paper, then the second and third ultrasonic measurements were taken. The second researcher repeated the third ultrasonic measurement to evaluate the interobserver variation. All specimens were sectioned and the remaining enamel thickness was measured under polarized light microscope. Results. Pearson's correlation analysis showed a high level of intraobserver agreement for the ultrasonic measurements of the first researcher (r = .891, P < .000 initial; r = .690, P < .001 first abrasion; r = .885, P < .000 second abrasion). Third ultrasonic measurements of the first and second researchers were positively and significantly correlated with histological readings (r = .966, P < .000; r = .466, P = .039). Conclusions. The ultrasonic system used in this study was reliable in measuring enamel thickness.
Keywords: WEAR; ATTRITION; EROSION